Pelatihan Teknologi Budidaya Udang Sistem Polikultur pada Kelompok Tani Pembudidaya Udang Di Desa Tamarupa Kecamatan Mandalle Kabupaten Pangkep, Provinsi Sulawesi Selatan - Harlina, Harlina; Saenong, Muhammad; Hamdillah, Andi (Dewan Pimpinan Daerah (DPD) Perkumpulan Dosen Indonesia Semesta (DIS) Jawa Timur, 2021)
One of the villages in Pangkajene and Islands District is Tamarupa Village, Mandalle District, which is a coastal area. Most of the population are fish farmers. In this village, there is a shrimp farmer group